Necklace‐style radio‐transmitters are associated with changes in display vocalizations of male greater sage‐grouse. (5th June 2017) - Fremgen, Marcella R.; Gibson, Daniel; Ehrlich, Rebecca L.; Krakauer, Alan H.; Forbey, Jennifer S.; Blomberg, Erik J.; Sedinger, James S.; Patricelli, Gail L.
Abstract : Radio‐transmitters are used widely in wildlife research because they allow researchers to track individual animals and monitor their activity. However, to provide unbiased information about a population, transmitters must be deployed on a representative sample of animals and must not alter the behavior of the individuals. The greater sage‐grouse Centrocercus urophasianus has been studied intensively using radio‐transmitters for the last several decades. A previous study demonstrated that males fitted with necklace‐style radio‐transmitters could be less likely to attend breeding grounds than those without transmitters. However, how transmitters affect the behavior of males that do attend leks has not been investigated. Therefore, we investigated whether radio‐transmitters alter the characteristics of strut vocalizations or display frequency of male sage‐grouse. We measured time and frequency characteristics of vocalizations from six collared and seven non‐collared adult male sage‐grouse on three leks in south‐central Idaho, and for two collared and four non‐collared males from two leks in northern Nevada. Only one vocalization characteristic (maximum frequency of the primary whistle) differed between collared and non‐collared males across both populations. Collared males showed a lower maximum frequency of the primary whistle that typically fell outside the range of variation for non‐collared males. This was the only difference found in the sample from Nevada, while in Idaho, collared males also exhibited a narrower bandwidth for the primary whistle (lower maximum frequency and higher minimum frequency), a shorter primary whistle, and a shorter secondary coo than non‐collared males. Some acoustic characteristics of sage‐grouse strut vocalizations are linked to mate choice by females, and therefore our results suggest that collars could reduce male mating success by altering the production of breeding vocalizations. Therefore, we recommend using alternative attachment techniques for behavioral studies of male sage‐grouse.